PENGARUHPENERAPANSTRATEGI PEMBELAJARANAKTIF TYPETHE POWER OF TWO TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMPN 3 BATANG KAPAS - Amalia Putri (Jurnal Edukasi dan Penelitian Matematika, 2019)
Learning outcomes can be used as a benchmark to knowing the success of mastering a lesson. However, the learning outcomes of Grade students of VIII SMP 3 Batang Kapas are still low. One effort to overcome this problem is by applying the active learning type type The Power Of Two. This type of research is quasi-experiment with the Static Group Design research design. The instrument of this research is the final test. Sampling is done by Simple Random Sampling. Data analysis was carried out, namely t-test. The final test analysis shows the results of mathematics learning of students who learn the active learning strategies of The Power Of Two type better than the results of mathematics learning of students who learn with direct learning models. Means, the application of the active learning type The Power Of Two strategy has an effect on learning outcomes mathematics students.Keywords – Result of  Learning Mathematical,  Active Learning Strategy,The Power  Of Two